Practice Interpretation and the Foundation of Morality: Practice Interpretation and the Foundation of Morality - Mota Pinto, Sílvio (Revista de Filosofía, 2020)
Is it possible to provide a philosophical foundation for our moral practices? Or should we admit that the project of grounding morality failed? In this paper, I reexamine moral foundationalism. First, I describe the problem from the Aristotelian perspective and also from the Kantian viewpoint. Secondly, I discuss Nietzsche’s and Moore’s criticisms of the foundationalist project. Finally, I sketch a non-foundatinalist justification of the highest good by appealing to some of the later Wittgenstein’s theses about the norms of meaning in ordinary language.